REPRESENTATION OF HISTORICAL IDENTITY IN TRANSLATION (Journal of Pharmaceutical Negative Results, 2022)
We know that translation has served as a bridge in the establishment of friendly relations between peoples and nations around the world. The effective work of the world's translators in this regard is unparalleled. This article discusses the basics of how to give historical works in translation.